Hilmi Ziya's life and thought from 1928 to 1960, in relation to the political and religious developments in the republic of Turkey - Özberki, Ayşe R. (Thesis (M.A.)- Bogazici University. Institute for Graduate Studies in Social Scieences, 1986., 1986)
This is the study of Hilmi Ziya tllken's (1901-1974) thought in relation to the political and religious development in the Republic of Turkey. Hilmi Ziya Ulken is a representative example of the very first intellectuals of the young Turkish Nation. Much weight was given to his ideas about religion as religion is the core of the paradigma of his sociological views. On the other hand empasis was also given to men of ideas who have been influencial on Hilmi Ziya Ulken's thought or intellectual development. Finally the study exposes the continiuty of his ideas which changed in appearence only.